2017
DOI: 10.3758/s13428-017-0860-3
|View full text |Cite|
|
Sign up to set email alerts
|

Using machine learning to detect events in eye-tracking data

Abstract: Event detection is a challenging stage in eye movement data analysis. A major drawback of current event detection methods is that parameters have to be adjusted based on eye movement data quality. Here we show that a fully automated classification of raw gaze samples as belonging to fixations, saccades, or other oculomotor events can be achieved using a machine-learning approach. Any already manually or algorithmically detected events can be used to train a classifier to produce similar classification of other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
105
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(130 citation statements)
references
References 32 publications
1
105
0
1
Order By: Relevance
“…Although Komogortsev, Gobert, Jayarathna, Koh, and Gowda (2010) have previously written about manual classification that In fields were human classification until recently dominated, automated algorithms take over quickly. New classification techniques such as identification by topological characteristics (Hein & Zangemeister, 2017) and machine learning (Zemblys et al, 2017) are promising. Other new algorithms (based on classic techniques) can deal with smooth pursuit episodes (Larsson et al, 2015) or a large variety of noise levels (Hessels, Niehorster, et al, 2016b).…”
Section: Labels and The Role Of Instructions And Event Selection Rulesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although Komogortsev, Gobert, Jayarathna, Koh, and Gowda (2010) have previously written about manual classification that In fields were human classification until recently dominated, automated algorithms take over quickly. New classification techniques such as identification by topological characteristics (Hein & Zangemeister, 2017) and machine learning (Zemblys et al, 2017) are promising. Other new algorithms (based on classic techniques) can deal with smooth pursuit episodes (Larsson et al, 2015) or a large variety of noise levels (Hessels, Niehorster, et al, 2016b).…”
Section: Labels and The Role Of Instructions And Event Selection Rulesmentioning
confidence: 99%
“…Manual classification to teach artificial intelligence (AI) and to develop algorithms Zemblys et al (2017) wrote: BAny already manually or algorithmically detected events can be used to train a classifier to produce similar classification of other data without the need for a user to set parameters^. It would be interesting if machine learning is used to produce automated AI classifiers that have the ability to classify eye-tracking data for which no classical algorithm exists.…”
Section: Labels and The Role Of Instructions And Event Selection Rulesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the few algorithm that are capable of detecting saccades as well as PSO 31,32,42 , U'n'Eye achieves highest performance. Note that Zemblys et al 42 reported higher absolute Cohen's kappa values for saccade and PSO detection, but obtained these on cleaner data than the benchmark dataset from Andersson et al 29 . As their dataset was not available to us, we were not able to assess U'n'Eye's performance on the same data.…”
Section: Discussionmentioning
confidence: 99%
“…To remove erroneous labels, we adapt the approach proposed by Zemblys et al 20 For our dataset, fixational events with <0.5 • separation between them and within 75ms of each other were combined into a single event. Fixations less than 50ms and saccades greater than 150ms in duration were automatically removed.…”
Section: Data Cleaning and Post-processingmentioning
confidence: 99%